THE LEVEL OF PHARMACOECONOMICS KNOWLEDGE AND THE APPLICATION OF PHARMACOECONOMICS IN PHARMACEUTICAL FIELDS AMONG PHARMACISTS IN INDONESIA. - Amalia, Fadillah
Pharmacoeconomics is a supporting knowledge that pharmacists need in order to fulfill their role in controlling healthcare financing, particularly the financing of pharmaceutical products. In Indonesia itself, pharmacoeconomics is considered a relatively new field, so the level of mastery and application of pharmacoeconomics in Indonesia is not yet known. This study was conducted to analyze the level of knowledge and application of pharmacoeconomics among pharmacists in pharmaceutical work in Indonesia. The study was conducted using a cross-sectional observational method by distributing a questionnaire that measured the level of knowledge, application, and education related to pharmacoeconomics. The questionnaire was completed by 469 respondents, and the research results showed that 65.03% (n = 305) of respondents had poor knowledge, and only 24.94% (n = 109) of respondents applied the principles of pharmacoeconomics in their work. Analysis using the Kruskal-Wallis method showed significant differences in knowledge scores among respondent groups categorized by age, year of graduation from the pharmacist professional study program, field of work, length of employment, and experience in learning pharmacoeconomics. It was also found that the group of respondents who applied pharmacoeconomics the most were pharmacists working in the community pharmacy field, with a total of 60 individuals, while the group of respondents who applied pharmacoeconomics the least were pharmacists working in the government sector. The research results indicate that the level of knowledge among pharmacists in Indonesia regarding pharmacoeconomics and its application in pharmaceutical work is still low, indicating the need for continuous education related to pharmacoeconomics.